Utility of algorithm‐based chemoradioselection in the treatment for advanced hypopharyngeal carcinoma. Issue 9 (24th July 2014) - Masuda, Muneyuki; Matsuo, Mioko; Aso, Takeichiro; Kiyohara, Hideyuki; Rikimaru, Fumihide; Kunitake, Naonobu; Higaki, Yuichiro
Abstract Background Current organ‐preserving dose‐intensified modalities have apparently reached the limit of human tolerance. To optimize the therapeutic ratio, we evaluated the utility of a chemoradioselection strategy for the treatment of advanced hypopharyngeal carcinoma. Methods Fifty‐five patients with advanced hypopharyngeal carcinoma were enrolled in our algorithm‐based protocol. After 40 Gy of concurrent chemoradiation therapy (CCRT), patients who were chemoradioselected (chemoradioselected group, complete response [CR] at the primary site) received further 30 Gy of CCRT up to 70 Gy, whereas the remaining nonchemoradioselected (nonchemoradioselected group) patients underwent radical surgery. Results Based on this algorithm, 27 patients were chemoradioselected and 28 nonchemoradioselected. The 5‐year cumulative disease‐specific and overall survival (OS) rates were 76% and 65%, respectively. The chemoradioselected group demonstrated favorable laryngoesophageal dysfunction‐free survival (77% at 3 years). Conclusion Although preliminary, our results indicate that algorithm‐based chemoradioselection may provide a novel platform for improving the treatment of advanced hypopharyngeal carcinoma by providing the complete advantages of CCRT and radical surgical resection. © 2014 Wiley Periodicals, Inc. Head Neck 37: 1290–1296, 2015